Establishing content validity of an instrument measuring content knowledge of an intervention program for adolescents living with HIV - Lourdunathan, Pamilia; Mohamad, Mardiana; Abdul Rahman, Shukran; Alwi, Azlin (2018)
This paper seeks to explore the dynamics underlying the wellbeing factors in the organization and workers’ psychological well-being. Considering the degree and impact of inequality among various communities, the high-demanding workloads in relation to work demands and out-of-work life challenges, it is pertinent that the well- being of every employee is central to the success and improvement of any organization. Positive psychology, in support to other aspects of mainstream psychology, has spread across disciplines like education, organizational functioning, career counseling, mental health, and human resource. It offers some valuable resources through flow and meaning that helps fosters the well-being of the employee and optimum productivity within the work setting. From review of related studies, experiencing optimal experience or being in a state of flow in situations of everyday life puts the worker in better psychological state when going through challenging periods. However, this positive momentum is yet to be felt in non-Western societies in both research and practice. While academicians need to invest greater attention in this area, it is recommended that managers and corporate bodies have to volte-face ways of improving productivity and performance at work towards making employees work more meaningful, and exploring measures to in-build amenities towards making workers to attain flow experience.